Flavonoids as Antidiabetic Agents, Challenges and Future Directions - Qamar Uddin Ahmed (Journal of Pharmacy, 2025)
Diabetes is a global health concern, affecting hundreds of millions of people worldwide. The number of adults living with diabetes has risen dramatically, from approximately 200 million in 1990 to nearly 589 million in 2024. Type 2 diabetes (T2DM) accounts for 90% of all cases. The incidence is increasing more rapidly in low- and middle-income countries than in high-income countries. By 2050, the number of people with diabetes is likely to reach over 853 million. Diabetes was the ninth leading cause of death globally in 2020, contributing to over 2 million deaths annually. In 2021, diabetes and kidney disease due to diabetes were responsible for more than 2 million deaths, and approximately 11% of cardiovascular deaths were associated with high blood glucose (International Diabetes Federation, 2025).